A program risk assessment method for aviation technology transitions - Gibbs, Jonathan Marcus (Massachusetts Institute of Technology, 2011)
Thesis (S.M.)--Massachusetts Institute of Technology, Dept. of Aeronautics and Astronautics, 2011. Cataloged from PDF version of thesis. Includes bibliographical references (p. 286-287). This work presents a method for assessing the potential impacts of program risks on aviation technology transitions. It first establishes a framework that provides a methodology to complete the assessment of those risks. Next, the framework is applied to a technology transition to data link and reduced separation procedures in the North Atlantic airspace for commercial and business aircraft. This transition is facilitated by the International Civil Aviation Organization (ICAO) and supported by the Air Navigation Service Providers (ANSPs) and other state authorities within the North Atlantic airspace. The assessment identified the most influential risks for each stakeholder impact category, mitigation difficulty, and highlighted the ways each risk influenced other risks. In total, 24 risks were identified. The assessment found that the risks were highly connected and influenced several stakeholder impact categories simultaneously. Out of the five risks with the highest aggregate stakeholder impact, only one also had a high likelihood of occurrence. by Jonathan Marcus Gibbs. S.M.